Impact of Type 2 Diabetes on Impaired Kidney Function in Sub-Saharan African Populations - Adebamowo, Sally N.; Adeyemo, Adebowale A.; Tekola-Ayele, Fasil; Doumatey, Ayo P.; Bentley, Amy R.; Chen, Guanjie; Zhou, Jie; Shriner, Daniel; Fasanmade, Olufemi Adetola; Okafor, Godfrey; Eghan, Benjamin; Agyenim-Boateng, Kofi; et al. (Frontiers in Endocrinology, 2016)
Abstract Background: Diabetes is a leading risk factor for impaired kidney function, an indicator of chronic kidney disease. The aim of this study was to examine the association between type 2 diabetes (T2D) and impaired kidney function among adults in sub-Saharan Africa (SSA). Methods: Participants were enrolled from Ghana, Kenya and Nigeria. Impaired kidney function was based on an estimated glomerular filtration rate (eGFR) < 60 ml/min/1·73m2. Using logistic regression models, we conducted case-control analyses to estimate the multivariate adjusted association of T2D and kidney function. Results: We used data from 4,815 participants for whom the mean (SD) age was 48 (15) years, 41% were male and 46% had T2D. Those with T2D were more likely to have impaired kidney function (13·4% [95% CI: 11·9 - 14·7]) compared to those without T2D (4·8% [95% CI:4·0 - 5·6]), p-value <0·001. The multivariate odds ratio of impaired kidney function among those with type 2 diabetes was 1·50 (95% CI: 1·17 - 1·91) p-value = 0.001, compared to those without T2D. Also, individuals with T2D who were at least 60 years old, obese, hypertensive or dyslipidemic were more likely to have impaired kidney function, compared to those without T2D. Conclusions: T2D was associated with 50% increased risk of impaired kidney function in this sample of adults from SSA. Interventions targeted at prevention, early diagnosis and management of T2D are likely to reduce the burden of kidney disease in SSA.